Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Impact of extreme flood on fecal and metal contamination in Lake Guaíba, southern Brazil - Juliana Schmitt de Nonohay; Simone Caterina Kapusta; Guilherme Gomes Ferrioli; Thaís Dalzochio; Roberta Plangg Riegel; Marco Antonio Siqueira Rodrigues; Luciano Basso da Silva (Limnologica, 2026)

Cryopreservation-induced proteomic alterations in Pêga donkey (Equus asinus) spermatozoa - Camilo Jose Ramirez-Lopez; Isabella Cristina Tolêdo Alves Costa; Wassali Valadares de Sousa; Yara Martins da Silva; Faider Alberto Castano Villadiego; Tayna Bolsam da Silva; Renner Philipe Rodrigues Carvalho; Arabela Guedes de Azevedo Viana; Jose Carlos Montes-Vergara; Mariana Machado-Neves; Simone Eliza Facioni Guimaraes; Fabio Cesar Sousa Nogueira; et al. (Cryobiology, 2026)

Effect of household cooking on aflatoxin B 1 migration in black beans: insights from bio-accessibility and intestinal transport - Simone Santos Soares; Caroline de Almeida Senna; Salvador da Silva Madruga Junior; Maristela Barnes Rodrigues Cerqueira; Eliana Badiale Furlong; Larine Kupski (Food Additives & Contaminants: Part A, 2026)

Abscisic Acid Modulates Physiological and Proteomic Changes During Histodifferentiation and Germination of Somatic Embryos in Euterpe edulis - Débora Pellanda Fagundes; Joana Silva Costa; Jociel Nascimento de Noronha; Mateus Santana Rodrigues; Caroline Palacio de Araujo; Simone Wellita Simão de Carvalho; Ingridh Medeiros Simões; Jéssica Batista Ribeiro e Oliveira; Edilson Romais Schmildt; Elias Terra Werner; Marcia Flores da Silva Ferreira; Amir Ali Khoddamzadeh; et al. (Journal of Plant Growth Regulation, 2026)
Euterpe edulis Martius (juçara palm) is an endangered species of high ecological and economic importance. Its propagation via reproduction is limited by the recalcitrance of its seeds, which hinders conservation and genetic improvement. Somatic embryogenesis represents an efficient alternative for large-scale clonal propagation and conservation. The present study evaluated the effect of abscisic acid (ABA) on histodifferentiation and germination of somatic embryos, to optimize in vitro regeneration of E. edulis . High rates of histodifferentiation (~ 98%) and germination (~ 95%) were achieved with 5 µM ABA, resulting in vigorous embryos with well-developed haustoria. Higher ABA concentrations (10–15 µM) were associated with reduced germination and delayed developmental progression, whereas the absence of ABA impaired histodifferentiation and embryo vigor. Proteomic profiling revealed increased accumulation of structural proteins (β-TUB7, TUBB1, TUBB5), chaperones (HSP83), proteasome components (PSMA2-like), energy metabolism enzymes (GAPDH2, PFK, PFP-α), tricarboxylic acid/glyoxysomal enzymes (SDH5, MDH-glyox), and nitrogen/methylation enzymes (GS, AHCY) in embryos treated with 5 µM ABA, suggesting associations with cytoskeletal remodeling, mitochondrial stability, epigenetic adjustments, and selective translation. In contrast, a decrease in defense proteins such as PR1 reflected a typical developmental trade-off. ABA also involves the integration of hormonal adjustments and the regulation of antioxidant enzymes. In summary, 5 µM ABA promotes efficient histodifferentiation and germination of embryos, enabling in vitro cloning, conservation, and genetic improvement of the species.

Integrated reverse osmosis and electrochemical oxidation for the removal of pharmaceuticals and antimicrobial-resistant bacteria from real hospital wastewater: efficiency, concentrate management, and environmental risk assessment - Diego U. Rizzana; Lucas Hansen; Tatiana K. Silva; Simone U. Picoli; Luciano B. da Silva; Marcos F. Debastiane; Rafael Liden; Andrea M. Bernardes; Louidi L. Albornoz; Salatiel W. da Silva; Alexandre Giacobbo; Marco A.S. Rodrigues (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Conservation gaps and the essential role of Indigenous Lands in protecting small non-volant mammals in Brazilian Amazonian” [ J. Nat. Conserv. 91 (2026) 127242] - Simone Almeida Pena; Cláudia Regina da Silva; Rafaela Jemely Rodrigues Alexandre; Thiago Bernardi Vieira (Journal for Nature Conservation, 2026)

Effects of Low-Intensity Aaerobic Training on Cardiac Dysfunction and Myocardial Fibrosis Induced by Doxorubicin in Wistar Rats - Talita Cristina Rodrigues Pereira; Alinne Tatiane Faria Silva; Matheus Matioli Mantovani; Simone Ramos Deconte; Bruno Antônio Ferreira; Mariane Marques da Guarda Pinto; Paulo Ricardo Lopes; Taysa Machado Menezes; Thiago Montes Fidale; Yara Cristina de Paiva Maia; Elmiro Santos Resende (Cardiovascular Toxicology, 2026)
Doxorubicin-induced cardiotoxicity is a major limitation in cancer therapy. Physical exercise has been proposed as a non-pharmacological strategy capable of mitigating these effects through cardiovascular adaptations. This study evaluated whether low-intensity aerobic training attenuates cardiac dysfunction induced by doxorubicin. Twenty-five adult male Wistar rats (450 and 500 g) were allocated and divided into four groups: Control (C), Doxorubicin (D), Doxorubicin and Trained (DT), and Trained (T). The D and DT groups received weekly intraperitoneal injections of doxorubicin over a four-week period, totaling a cumulative dose of 8 mg/kg. The DT and T groups underwent low-intensity aerobic training for 25 weeks, three times a week, with sessions lasting 10 to 20 min at 50 and 60% of maximum aerobic speed. Statistical analysis was performed using GraphPad Prism software (version 8.0). The D group showed a significant increase in myocardial collagen deposition and a reduction in S wave values (parietal and septal) on echocardiography, compared to the control group. The values observed were 0.040 for group D and 0.065 for group C in the parietal S wave (overall p = 0.0248), and 0.040 for group D and 0.070 for group C in the septal S wave (overall p = 0.0389). Regarding exercise tolerance, group D showed the greatest reduction in performance from Test 0 to Test 5 (65.06%; p < 0.0001), followed by group C (23.60%; p = 0.0103). Group DT showed a smaller numerical reduction in performance (23.07%), but this change did not reach statistical significance ( p = 0.1256), while group T showed a non-significant numerical improvement (10.99%; p = 0.2020). The results suggest that low-intensity aerobic training may attenuate cardiac fibrosis and partially preserve functional capacity in rats with doxorubicin-induced cardiotoxicity. Graphical Abstract Doxorubicin-induced cardiotoxicity increases myocardial fibrosis and promotes cardiac remodeling compatible with cardiac dysfunction. In this study, low-intensity aerobic exercise appeared to attenuate collagen accumulation and partially preserve functional parameters in Wistar rats exposed to doxorubicin. Echocardiographic and histological analyses revealed preserved systolic function and reduced deposition of type I and III collagen in animals that received doxorubicin and underwent training. These findings suggest that low-intensity aerobic training may act as a protective strategy, by mitigating myocardial remodeling and contributing to better tolerance to doxorubicin-induced injury.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Conservation gaps and the essential role of Indigenous Lands in protecting small non-volant mammals in Brazilian Amazonian - Simone Almeida Pena; Cláudia Regina da Silva; Rafaela Jemely Rodrigues Alexandre; Thiago Bernardi Vieira (Journal for Nature Conservation, 2026)

Investigation of EU-priority polycyclic aromatic hydrocarbons in wheat flour and baked products: Implications for food safety - Glória Maria Guizellini; Simone Alves da Silva; Adriana Palma de Almeida; Rosana Aparecida Manólio Soares-Freitas; Elizabeth Aparecida Ferraz da Silva Torres; Olga Maria da Silva Viegas; Edgar Pinto; Geni Rodrigues Sampaio (Food Research International, 2026)

Intensified tropical pasture-based beef cattle production systems and their effects on carcass traits, meat quality and methane emissions from Nellore steers - Gabriele Voltareli da Silva; Rolando Pasquini Neto; Mariana Nunes Vieira de Melo; Luiza Budasz de Andrade; Althieres José Furtado; Ester Costa Fabricio; Analisa Vasques Bertoloni; Annelise Aila Gomes Lobo; Flavio Perna Junior; Sérgio Raposo de Medeiros; Alexandre Berndt; Renata Tieko Nassu; et al. (Livestock Science, 2026)

Image-based phenotyping of castor bean seeds for morphological traits, seed weight prediction, and assessment of genetic diversity - Diego Andrade Santos; Diego Fernando Marmolejo Cortes; Mylena Almeida dos Santos; Myriam El Adas; Bismarck Ferreira de Morais; Denise Barreto dos Santos; Tairone da Silva de Almeida; Christian Adalberto Santos de Queiroz; Gabriel da Paixão Fernandes; Ailan Santos de Jesus; Rafaella da Silva Rodrigues; Daniel Santos Alves; et al. (Euphytica, 2026)
Digital seed phenotyping offers an efficient and objective alternative to conventional, labor-intensive methods for morphological characterization in plant breeding programs. In castor bean, rapid and reliable tools are essential to support genetic improvement. This study evaluated the potential of digital phenotyping for seed characterization and its application in breeding. Seeds from 65 accessions (2023) and 51 accessions (2024) were photographed with an RGB camera and processed in ImageJ® for extraction of morphological traits. Agreement between digital and manual measurements was assessed by correlation and Bland–Altman analysis, while machine learning models were trained to predict hundred-seed weight (HSW). Genetic diversity was explored using principal component analysis (PCA) and clustering, and variance components and heritability were estimated with mixed linear models. Digital phenotyping showed strong agreement with manual measurements (r = 0.95–0.97) and enabled accurate HSW prediction, with Ridge Regression achieving the best performance (R 2 = 0.88; RMSE = 3.83; MAE = 3.19). PCA explained 85.7% of the variance and revealed three phenotypic clusters. Traits such as seed length (H 2 = 0.88) and aspect ratio (H 2 = 0.87) exhibited high heritability, while roundness (H 2 = 0.79), perimeter (H 2 = 0.72), and area (H 2 = 0.67) were moderate. These findings demonstrate that digital phenotyping is a reliable and high-throughput method for castor bean seed characterization, supporting genotype selection and the integration of machine learning approaches into breeding programs for greater precision and efficiency.

Virulence and Immune Response of Campylobacter jejuni Strains in Chicken Embryo Model - Paula Fernanda de Sousa Braga; Emília Rezende Vaz; Simone Sommerfeld; Fabiana de Almeida Araújo Santos; Gabriela Ribeiro da Silva; Alessandra Castro Rodrigues; Isabelle Ezequiel Pedrosa; Alessandra Aparecida Medeiros Ronchi; Adriana Freitas Neves; Belchiolina Beatriz Fonseca (Current Microbiology, 2026)
This study aimed to evaluate the virulence and infection response of Campylobacter jejuni (CJ) strains isolated from chickens, as well as a standard strain isolated from humans, to understand better the pathogen-host relationship between CJ and chicken embryos (CE) with an active immune system. With its well-developed vascular structures, the CE model offers a valuable method for studying complex biological systems. We assessed embryo mortality, weight, macroscopic and microscopic lesions, bacterial multiplication within the embryo, and macrophage and lymphocyte (T and B cell) counts using flow cytometry. Additionally, histopathological lesions were examined. CJ killed CE at a dose of 3.7 log CFU/CE; however, lower doses (2.5 log CFU/CE) did not result in embryo death but instead caused macroscopic damage along with mild to moderate lesions. Certain strains were also capable of stimulating the immune system; however, this response varied depending on the strain. These findings underscore the importance of studying the virulence, infection dynamics, and immune responses of various CJ strains, highlighting the utility of the CE model for these investigations.

Brazil’s climate leadership paradox: hosting COP30 amid domestic environmental rollbacks - Daniela Debone; Ronan Adler Tavella; Mariana Vieira da Costa; Eliane Seiko Maffi Yamada; Flavio Manoel Rodrigues da Silva Júnior; Sandra de Souza Hacon; Paulo Artaxo; Simone Georges El Khouri Miraglia (International Environmental Agreements: Politics, Law and Economics, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Obtaining and characterizing bacuri (Platonia insignis) seed flour: a strategy for valuing fruit co-products from a sustainable food perspective - Simone Kelly Rodrigues Lima; Luiz Brito de Souza Filho; José Otávio Carvalho Sena de Almeida; José Moreira Tavares Neto; Michel Muálem de Moraes Alves; Arkellau Kenned Silva Moura; Antônia Maria das Graças Lopes Citó; Francisco Cardoso Figueiredo; Leandro Josuel da Costa Santos; Liduína Soares de Carvalho Mendes; André Filipe Sousa Loiola; Joyce Lopes Macedo; et al. (Food Chemistry, 2026)

Advances in chitosan/gelatin scaffold design: Bridging manufacturing, crosslinking, and structure - Function dynamics - Monize Gabriella Cesquim; Lilian Rodrigues Lopes; Larissa Dionísio da Silva; Maryana Bizarria da Silva; Giovanni Davide Donato; Willian Fragali Machado; Pedro Bernardes Noronha; Layde Teixeira de Carvalho; Simone de Fátima Medeiros (Carbohydrate Polymers, 2026)

Investigation of Phytol as an Inhibitor of the Efflux Pump (QacA/B) in Staphylococcus aureus: in silico and in vitro Studies - José Weverton Almeida-Bezerra; Carlos Alonso Leite dos Santos; Saulo Almeida Menezes; Cícera Datiane de Morais Oliveira-Tintino; Rafael Pereira da Cruz; Adrielle Rodrigues Costa; Janaína Esmeraldo Rocha; Daniel Sampaio Alves; Simone Galdino de Sousa; Ewerton Yago de Sousa Rodrigues; Gabriel Gonçalves Alencar; José Maria Barbosa Filho; et al. (Pharmaceutical Research, 2026)

Integrated in Vitro, in Vivo, Molecular Docking, and ADMET in Silico Assessment of β-Caryophyllene as a NorA Efflux Pump inhibitor in Resistant Staphylococcus Aureus (MRSA) - José Weverton Almeida-Bezerra; José Thyálisson da Costa Silva; Cícera Datiane de Morais Oliveira-Tintino; Adrielle Rodrigues Costa; Viviane Bezerra da Silva; Maria Flaviana Bezerra Morais-Braga; Irwin Rose Alencar de Menezes; Ana Carolina Ferreira Araujo; Lucas Yure Santos da Silva; Daniel Sampaio Alves; Guilherme Fernandes Teixeira; Lucas dos Santos Sa; et al. (Current Microbiology, 2026)

Development of CND and DRIS Standards for High-Quality ‘Hass’ Avocado Seedling Production - Marcelo Almeida de Oliveira Junior; Danilo Eduardo Rozane; Tatiana Cantuarias-Avilés; Simone Rodrigues da Silva (Journal of Soil Science and Plant Nutrition, 2025)

Antifungal activity of cephalosporins as an alternative for the combat of Candida auris - Milena Izabel dos Santos Rodrigues; Fabíola Lucini; Gabrieli Argueiro da Silva; Mariana Carvalho Sturaro; Osmar Nascimento Silva; Thiago Mendonça de Aquino; Lavinia Leite Pintan Careaga; Alex Polatto Carvalho; Fabricio Fagundes Pereira; Simone Simionatto; Luana Rossato (Brazilian Journal of Microbiology, 2025)

Impact of Climate Change-Mediated Tragedies: An Account of Extreme Rainfall Event in Rio Grande do Sul, Brazil - Daniela Debone; Ronan Adler Tavella; Arnaldo Lopes Colombo; Ana Cristina Gales; Flávio Manoel Rodrigues da Silva Júnior; Simone Georges El Khouri Miraglia (Anthropocene Science, 2025)

Technical Note: Different analytical approaches in the quantification of microbial crude protein pool in abomasal digesta of nursling goat kids - Jardeson de Souza Pinheiro; Paulo Sergio Dornelas Silva; Isadora Emily Ribeiro; Dhones Rodrigues Andrade; Natalia Veloso Trópia; Yame Fabres Robaina Sancler-Silva; Erollykens Ferreira Santos; Giarlã Cunha da Silva; Simone Eliza Facione Guimarães; Marcos Inacio Marcondes (Animal Feed Science and Technology, 2025)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

‘Carmen Hass’: A New ‘Hass’-Like Avocado Option in Southeast Brazil - Lígia Broglio Micheletti; Tatiana Cantuarias-Avilés; Marcelo Almeida de Oliveira Junior; Edypol Guilherme Baptista; Guilherme Nacata; Simone Rodrigues da Silva (Applied Fruit Science, 2025)

Anatomical traits of epicarp and pericarp in Eugenia involucrata and Eugenia pyriformis: potential implications for postharvest behavior - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Sandra Maria Carmello-Guerreiro; Simone Rodrigues da Silva; Francisco de Assis Alves Mourão Filho (Brazilian Journal of Botany, 2025)

A population under smoke: fire events trigger severe air pollution in Portugal - Simone Georges El Khouri Miraglia; Daniela Debone; Clara Lopes Ribeiro; Rui Moreira Barbosa; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva-Júnior; Manuela Vieira da Silva; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Epidemiological surveillance in congenital anomalies and rare diseases in Brazil: present situation and future challenges - Lavínia Schuler-Faccini; Simone de Menezes Karam; Maria Teresa Vieira Sanseverino; Marcia Helena Barbian; Julia do Amaral Gomes; João Matheus Bremm; Augusto César Cardoso-dos-Santos; Claudia Fernandes Lorea; Karina Carvalho Donis; Ricardo Rohweder; Laércio Moreira Cardoso-Junior; Julia Cavalcante do Carmo; et al. (Journal of Community Genetics, 2025)

Temporal dynamics of guava root-knot nematode under the effect of different management methods - Isadora Rodrigues Garcia Gondo; Matheus Ricardo da Rocha; Cayo Yoshihiro Gondo; Kaique dos Santos Alves; Breno Benvindo dos Anjos; Simone de Paiva Caetano Bucker Moraes; Guilherme de Rezende Camara; Moises Zucoloto; Dimmy Herllen Silveira Gomes Barbosa; Fábio Ramos Alves; André da Silva Xavier; Samuel de Assis Silva; et al. (Crop Protection, 2025)

An exploratory study on the association between air pollution and health problems (ICD-10) with an emphasis on respiratory diseases - Ronan Adler Tavella; Julia Oliveira Penteado; Rodrigo de Lima Brum; Alicia da Silva Bonifácio; Meister Coelho San Martin; Elizabet Saes-Silva; Aline Neutzling Brum; Romina Buffarini; Washington Luiz Félix Correia Filho; Diana Francisca Adamatti; Rosália Garcia Neves; Edmilson Dias de Freitas; et al. (Atmospheric Pollution Research, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Vibrational spectroscopic techniques and variable selection in Linear Discriminant Analysis to geographical origin discrimination of Jatropha mollissima sap - Caroline Lins Fernandes; Tiago Santos Silva; Caike Lobo Rodrigues de Lima; Isabel Cristina Vicente dos Santos; Djair Araújo Fialho; Marcus Vinicius Lia Fook; Paulo Henrique Gonçalves Dias Diniz; José Filipe Bacalhau Rodrigues; Simone da Silva Simões (Phytochemistry Letters, 2024)

Water exchange rate and stocking density on the larviculture of the scallop Nodipecten nodosus in recirculation aquaculture system - Simone Sühnel; Francisco José Lagreze Squella; Francisco Carlos da Silva; Claudio Manoel Rodrigues de Melo (Aquaculture, 2024)

Antimicrobial efficiency of bromhexine hydrochloride against endometritis-causing Escherichia coli and Trueperella pyogenes in bovines - Bruna Matzembacker; Dyeison da Silva Fantinel; Claudia Medeiros Rodrigues; Samara Pereira da Silva; Matheus Henrique Dal Bó Marin; Danillo Sales Rosa; Mateus Matiuzzi da Costa; Simone Silveira; Lilian Kolling Girardini (Brazilian Journal of Microbiology, 2024)

Stocking Density and Diet of Two Oyster (Crassostrea gasar and Crassostrea gigas) Seeds in Fluidized Bed Bottle Nursery System - Simone Sühnel; Francisco José Lagreze-Squella; Gabriel Nandi Corrêa; Jaqueline Araújo; Glauber de Souza; João Paulo Ramos Ferreira; Francisco Carlos da Silva; Carlos Henrique Araújo de Miranda Gomes; Claudio Manoel Rodrigues de Melo (Fishes, 2024)
Crassostrea is the most farmed oyster genus worldwide and has significant economic and social impacts with environmental benefits. Hatchery oyster seed production is a highly costly phase, and a fluidized nursery system can help reduce this cost and reduce seed production time. The present study evaluated the survival and growth of two oyster species (Crassostrea gasar and Crassostrea gigas) in a fluidized bed bottle nursery system. With C. gasar, two experiments were performed; one tested three stocking densities and the other three bialgae diets. With C. gigas, one experiment with a bialgae and monoalgae in an initial bottle occupation of 8.8% produced more seeds per bottle, but an initial bottle occupation of 2.2% produced bigger seeds. Also, the experiment with C. gasar and with C. gigas tested diets did not affect seed survival, but the diets with bialgae I. galbana and N. oculate promoted more seed growth. The fluidized bed bottle nursery system developed for this study was adequate for the seeds of the oysters C. gasar and C. gigas in the nursery phase.

Aqueous enzymatic extraction of macauba (Acrocomia aculeata) pulp oil: A green and sustainable approach for high-quality oil production - Guilherme Dallarmi Sorita; Simone Palma Favaro; Dasciana de Sousa Rodrigues; Wellington Paula da Silva Junior; Wesley Gabriel de Oliveira Leal; Alan Ambrosi; Marco Di Luccio (Food Research International, 2024)

Development and properties of biodegradable film from peach palm (Bactris gasipaes) - Rebeca Desireé Sousa da Costa; Simone Hickmann Flôres; Adriano Brandelli; Carolina Galarza Vargas; Ana Carolina Ritter; Antonio Manoel da Cruz Rodrigues; Luiza Helena Meller da Silva (Food Research International, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Phytochemical analysis of Brugmansia suaveolens Bercht. & J. Presl and its therapeutic potential for topical use - Sandro Pinheiro da Costa; Raphaela Aparecida Schuenck-Rodrigues; Verônica da Silva Cardoso; Simone Sacramento Valverde; Alane Beatriz Vermelho; Eduardo Ricci-Júnior (Natural Product Research, 2023)

The kombucha ingestion benefits on the intestinal microbiota - Iraíldo Francisco Soares; Michele Alves de Lima; Massimo Lucarini; Alessandra Durazzo; Daniel Dias Rufino Arcanjo; Simone Kelly Rodrigues Lima; Robson Alves da Silva (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Embryotoxicity of silica nanoparticles in the drug delivery of domperidone in zebrafish - Lorranny Pereira de Assis Valadares; Larise Caroline Oliveira Lima; Simone Maria Teixeira de Saboia-Morais; Tatiane Moraes Arantes; Fernando Henrique Cristovan; Naiton Martins da Silva; Aline Borges Andrade; Sandra Aparecida Benite Ribeiro; Benner Geraldo Alves; Barbara do Carmo Rodrigues Virote; Ives Charlie da Silva; Mônica Rodrigues Ferreira Machado (Aquatic Toxicology, 2023)

Concentration and potential health risk of polycyclic aromatic hydrocarbons for consumers of chocolate in Brazil - Glória Maria Guizellini; Geni Rodrigues Sampaio; Simone Alves da Silva; Rosana Aparecida Manólio Soares-Freitas; Adriana Palma de Almeida; Elizabeth Aparecida Ferraz Da Silva Torres (Food Chemistry, 2023)

Multiresistant bacteria isolated from domestic and wild animals with skin lesions were susceptible to native plants from Southern Brazil - Claudia Giordani; Stefanie Bressan Waller; Karina Affeldt Guterres; Cristine Cioato da Silva; Raulene Rodrigues Lobo; Jéssica Fernanda Hoffmann; Soliane Carra Perera; Fábio Clasen Chaves; Sílvia Regina Leal Ladeira; Eliza Simone Viegas Sallis; Gilberto D’Ávila Vargas; Marlete Brum Cleff (Natural Product Research, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Three challenging cases of infections by multidrug-resistant Serratia marcescens in patients admitted to intensive care units - Kesia Esther da Silva; Luana Rossato; Sérgio Jorge; Natasha Rodrigues de Oliveira; Frederico Schmitt Kremer; Vinícius Farias Campos; Luciano da Silva Pinto; Odir Antonio Dellagostin; Simone Simionatto (Brazilian Journal of Microbiology, 2021)

Identification and validation of SNPs in the phytoene synthase 2 (psy2) gene associated with yellow color of the root in cassava (Manihot esculenta Crantz) accessions of the Brazilian Amazon - Francisca Chagas Bezerra das Araújo; Elisa Ferreira Moura; Simone Miranda de Rodrigues; Kenny Bonfim Arruda de Carvalho; Eraldo José Madureira Tavares; Mônika Fecury Moura; Gilvan Ferreira da Silva (Genetic Resources and Crop Evolution, 2021)

Determination of trace elements in the nanometer, ultrafine, fine, and coarse particulate matters in an area affected by light vehicular emissions in the city of Rio de Janeiro - Simone Lorena Quiterio de Souza; Eduardo Monteiro Martins; Sergio Machado Corrêa; Josiane Loyola da Silva; Roger Rodrigues de Castro; Flávia de Souza Assed (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Campylobacter jejuni isolated from poultry meat in Brazil: in silico analysis and genomic features of two strains with different phenotypes of antimicrobial susceptibility - Simone de Fátima Rauber Würfel; Sérgio Jorge; Natasha Rodrigues de Oliveira; Frederico Schmitt Kremer; Christian Domingues Sanchez; Vinícius Farias Campos; Luciano da Silva Pinto; Wladimir Padilha da Silva; Odir Antônio Dellagostin (Molecular Biology Reports, 2020)

Prior exercise protects against oxidative stress and motor deficit in a rat model of Parkinson’s disease - Leonam Oliver Durval Oliveira; Pedro Iuri Castro da Silva; Renato Pereira Rodrigues Filho; Raphaely Cristiny Sanches Progênio; Victor Douglas Pereira Silva de Oliveira; Renata Cunha Silva; Mariseth Carvalho de Andrade; Jofre Jacob da Silva Freitas; Katia Simone Kietzer (Metabolic Brain Disease, 2020)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Effect of 1-MCP and low-temperature storage on postharvest conservation of camu–camu - Patrícia Maria Pinto; Poliana Cristina Spricigo; Simone Rodrigues da Silva; Steven Alonzo Sargent; Angelo Pedro Jacomino (Acta Physiologiae Plantarum, 2018)

Environmental Surveillance of Polioviruses in Rio de Janeiro, Brazil, in Support to the Activities of Global Polio Eradication Initiative - Joseane Simone de Oliveira Pereira; Lidiane Rodrigues da Silva; Amanda de Meireles Nunes; Silas de Souza Oliveira; Eliane Veiga da Costa; Edson Elias da Silva (Food and Environmental Virology, 2016)

Antinociceptive and wound healing activities of Croton adamantinus Müll. Arg. essential oil - Rafael Matos Ximenes; Lenise de Morais Nogueira; Nathalia Maria Rodrigues Cassundé; Roberta Jeane Bezerra Jorge; Simone Maria dos Santos; Lucimere Paulino Machado Magalhães; Monalisa Ribeiro Silva; Glauce Socorro de Barros Viana; Renata Mendonça Araújo; Kêsia Xisto da Fonseca Ribeiro de Sena; Julianna Ferreira Cavalcanti de Albuquerque; René Duarte Martins (Journal of Natural Medicines, 2013)

Freezing solution containing dimethylsulfoxide and fetal calf serum maintains survival and ultrastructure of goat preantral follicles after cryopreservation and in vitro culture of ovarian tissue - Simone Vieira Castro; Adeline Andrade de Carvalho; Cleidson Manoel Gomes da Silva; Luciana Rocha Faustino; Cláudio Cabral Campello; Carolina Madeira Lucci; Sônia Nair Báo; José Ricardo de Figueiredo; Ana Paula Ribeiro Rodrigues (Cell and Tissue Research, 2011)

A Study of Gene Expression in the Nematode Resistant Wild Peanut Relative, Arachis stenosperma, in Response to Challenge with Meloidogyne arenaria - Patricia Messenberg Guimarães; Ana Cristina Miranda Brasileiro; Karina Proite; Ana Claudia Guerra de Araújo; Soraya Cristina Macedo Leal-Bertioli; Aline Pic-Taylor; Felipe Rodrigues da Silva; Carolina Vianna Morgante; Simone da Graça Ribeiro; David John Bertioli (Tropical Plant Biology, 2010)